Arsenic in marine sediments from French Mediterranean ports: Geochemical partitioning, bioavailability and ecotoxicology - Mamindy-Pajany, Yannick; Hurel, Charlotte; Geret, Florence; Galgani, François; Battaglia-Brunet, Fabienne; Marmier, Nicolas; Roméo, Michele (Chemosphere, 2013)
International audience This work investigates arsenic mobility, bioavailability and toxicity in marine port sediments using chemical sequential extraction and laboratory toxicity tests. Sediment samples were collected from two different Mediterranean ports, one highly polluted with arsenic and other inorganic and organic pollutants (Estaque port (EST)), and the other one, less polluted, with a low arsenic content (Saint Mandrier port (SM)). Arsenic distribution in the solid phase was studied using a sequential extraction procedure specifically developed for appraising arsenic mobility in sediments. Toxicity assessment was performed on sediment elutriates, solid phases and aqueous arsenic species as single substance using the embryotoxicity test on oyster larvae (Crassostrea gigas) and the Microtox test with Vibrio fischeri. Toxicity results showed that all sediment samples presented acute and sub-chronic toxic effects on oyster larvae and bacteria, respectively. The Microtox solid phase test allow to discriminate As-contaminated samples from the less contaminated ones, suggesting that toxicity of whole sediment samples is related to arsenic content. Toxicity of dissolved arsenic species as single substance showed that Vibrio fischeri and oyster larvae are most sensitive to As(V) than As(III). The distribution coefficient (Kd) of arsenic in sediment samples was estimated using results obtained in chemical sequential extractions. The Kd value is greater in SM (450 L kg(-1)) than in EST (55 L kg(-1)), indicating that arsenic availability is higher for the most toxic sediment sample (Estaque port). This study demonstrates that arsenic speciation play an important role on arsenic mobility and its bioavailability in marine port sediments